2020
DOI: 10.3389/fcimb.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

Autoinducer-2 May Be a New Biomarker for Monitoring Neonatal Necrotizing Enterocolitis

Abstract: Autoinducer-2 (AI-2) has a widely accepted role in bacterial intra-and interspecies communication. Little is known about the relationships between AI-2 and NEC. This study found that AI-2 levels in patients and in a NEC mouse model were detected using the Vibrio harveyi BB170 assay system. Bacterial communities of the newborns' stool microbiota (NEC acute group, NEC recovery group, control group, and antibiotics-free group) and of the NEC mouse model (NEC group and control group) were detected by high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
7
23
0
Order By: Relevance
“…This finding was consistent with a meta-analysis of fecal microorganisms in NEC preterm infants (Pammi et al, 2017). At the genus level, we also found that the abundance levels of Clostridium_sensu_stricto_1 were significantly increased, and previous studies also found that Clostridium_sensu_stricto_1 is much more abundant in NEC infants (Fu et al, 2020). The proliferation of Clostridium species in the colon may produce toxins and lead to intestinal epithelial damage (Schönherr-Hellec and Aires, 2019).…”
Section: The Relation Between Nec and Intestinal Flora Disordersupporting
confidence: 91%
See 4 more Smart Citations
“…This finding was consistent with a meta-analysis of fecal microorganisms in NEC preterm infants (Pammi et al, 2017). At the genus level, we also found that the abundance levels of Clostridium_sensu_stricto_1 were significantly increased, and previous studies also found that Clostridium_sensu_stricto_1 is much more abundant in NEC infants (Fu et al, 2020). The proliferation of Clostridium species in the colon may produce toxins and lead to intestinal epithelial damage (Schönherr-Hellec and Aires, 2019).…”
Section: The Relation Between Nec and Intestinal Flora Disordersupporting
confidence: 91%
“…AI-2 levels were reduced in the acute stage and increased in the recovery stage of NEC. The AI-2 concentration inversely correlates with the degree of inflammation and microbial dysbiosis in NEC (Fu et al, 2020). In the present study, a similar phenomenon was observed in the mouse NEC model (Figure 3).…”
Section: The Relation Between Nec and Intestinal Flora Disordersupporting
confidence: 87%
See 3 more Smart Citations